Inconsistent social rhythms are associated with abdominal adiposity after involuntary job loss: An observational study. (21st January 2021) - Haynes, Patricia L.; Apolinar, Gabriella R.; Mayer, Candace; Kobayashi, Ume; Silva, Graciela E.; Glickenstein, David A.; Thomson, Cynthia A.; Quan, Stuart F.
Abstract: Objective: Unemployment is an established risk factor for obesity. However, few studies have examined obesity‐related health behavior after involuntary job loss specifically. Job loss confers a disruption in daily time structure that could lead to negative metabolic and psychological outcomes through chronobiological mechanisms. This study examines whether individuals with unstable social rhythms after involuntary job loss present with higher abdominal adiposity than individuals with more consistent social rhythms and whether this relationship varies as a function of depressive symptoms. Methods: Cross‐sectional baseline data ( n  = 191) from the ongoing Assessing Daily Activity Patterns in occupational Transitions (ADAPT) study were analyzed using linear regression techniques. Participants completed the Social Rhythm Metric‐17 (SRM) daily over 2 weeks. They also completed the Beck Depression Inventory II (BDI‐II) and participated in standardized waist circumference measurements (cm). Results: A significant interaction emerged between SRM and BDI‐II demonstrating that less consistent social rhythms were associated with larger waist circumference at lower levels of depressive symptoms. Additional exploratory analyses demonstrated a positive association between the number of daily activities performed alone and waist circumference when controlling for symptoms of depression. Conclusion: These findings are the first to demonstrate a relationship between social rhythm stability and abdominal adiposity in adults who have recently, involuntarily lost their jobs. Results highlight the moderating role of depressive symptoms on daily routine in studies of metabolic health. Future prospective analysis is necessary to examine causal pathways.